A qualitative analysis of free text comments of participants from a massive open online mindfulness course - Neate, Sandra L.; Reece, Jeanette C.; Hassed, Craig; Chambers, Richard; Connaughton, Sherelle; Nag, Nupur (Frontiers in Public Health, 2022)
Introduction Mindfulness-based interventions are associated with improved health and wellbeing. Online mindfulness interventions offer potential scalability and cost advantages over face-to-face interventions. However, little is known about the experiences of learners, what they identify as being helpful to developing a practice of mindfulness and what outcomes they experience from undertaking an online mindfulness program. Methods The Mindfulness for Wellbeing and Peak Performance Massive Open Online Course is a 4-week mindfulness program which includes psychoeducation, mindfulness meditation, applications and moderated discussion forums. Of the 3,335 participants who completed the March 2020 course, 527 (16%) responded to the final forum which invited participants to describe the highlights of the course. In order to enhance understanding of participant experiences and perceived outcomes of undertaking the course, a qualitative analysis of these free text comments was conducted using reflexive thematic analysis. Results Two overarching themes were identified: (1) internal mechanisms of developing mindfulness (subthemes: paying attention to the present moment, learning to let go and find acceptance, cultivating an attitude of gentleness, and learning through a sense of belonging) and (2) the translation of mindfulness into daily living (subthemes: mindfulness being a support to mental wellbeing, learning to deal with uncertainty and adversity, living a more conscious life, a greater connection with self and others and channeling attention into productivity). Discussion The themes and subthemes provided insights into the mechanisms learners used to develop mindfulness and how they translated mindfulness into their lives in a variety of beneficial ways. This understanding of learners' experiences could inform delivery of future online mindfulness interventions.